2018
DOI: 10.1111/dth.12722
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and management of iatrogenic blindness associated with aesthetical filler injections

Abstract: Injectable fillers have become one of the most performed aesthetical treatments worldwide over the past two decades. They are frequently applied to the face, offering effective and safe alternatives to more invasive surgical procedures. Nevertheless, there are serious risks associated with filler‐based treatment. Visual impairment stands as a rare yet catastrophic adverse event associated with intravascular embolization of injected material to the retina or other areas of the central nervous system; potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…Even though the efficacy and safety of aspirin and heparin have not been proven in hyaluronic acid related occlusions, studies have highlighted their potential of preventing thrombotic spreading [ 17 , 30 , 37 – 42 ]. The rationale behind the application of aspirin is based on extrapolation from other clinical settings, i.e.…”
Section: Discussion Of Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the efficacy and safety of aspirin and heparin have not been proven in hyaluronic acid related occlusions, studies have highlighted their potential of preventing thrombotic spreading [ 17 , 30 , 37 – 42 ]. The rationale behind the application of aspirin is based on extrapolation from other clinical settings, i.e.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…While Murray et al urge clinicians to consider potential risks of instituting steroid therapy, i.e. impaired wound healing and increased risk of infection [ 43 ], most studies acknowledge the potential of decreasing the inflammatory component of the injury [ 5 , 37 , 40 , 42 , 46 ].…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…Searching (not retrieved) 27. Prevention and management of iatrogenic blindness associated with aesthetical filler injections [70] Not related [71] Efficacy and safety of a hyaluronic acid filler to correct aesthetically detracting or deficient features of the Asian nose: a prospective, open-label, long-term study Not solid polymers 29. Application of a porous polyethylene spreader graft for nasal lengthening in Asian patients [72] Not dorsum separately 30.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that loss of vision is irreversible in most cases of ophthalmic vascular occlusion, and to date, no effective treatments have been developed. [ 8 ] Conventional treatments for spontaneous central retinal artery occlusion have been applied in the iatrogenic retinal artery occlusion. However, none of them showed favorable results.…”
Section: Discussionmentioning
confidence: 99%